Polycyclic aromatic hydrocarbons (PAHs) in seabird eggs in Ireland. (September 2021) - Power, Andrew; White, Philip; McHugh, Brendan; Berrow, Simon; McKeown, Aaron; Crowley, Denis; Newton, Stephen; McGovern, Evin; Murphy, Sinéad; O'Connor, Ian
Abstract: Seabird eggs are considered a favourable matrix for monitoring marine pollutants and are widely used as higher trophic level indicators. Concentrations of Polycyclic aromatic hydrocarbons ( Σ 15PAH) were determined in the eggs of four piscivorous seabirds in Ireland from multiple colonies for the first time, Common Guillemot Uria aalge, Northern Gannet Morus bassanus, Common Tern Sterna hirundo and Arctic Tern S. paradisaea. PAH concentrations were generally lower than levels detected in eggs from other seabird studies and considerably lower than concentrations associated with no adverse effect in the eggs of domestic avian species. This study indicates potential site and species differences in PAH concentrations. Baseline data of PAHs in a range of seabird species from this study may provide an important reference point should a major pollution event occur in European waters, such as an oil spill. Highlights: PAHs analysed in Irish seabird eggs for first time Species differences between Gannet, Guillemot, Common and Arctic Tern PAH concentrations below toxic thresholds Results provide reference point of baseline levels in case of pollution event